Churros Product Innovation With Cassava Raw Materials - Muhammad Nawawi; Siti Nur Ryza Novianti; Rifanti Barnia (MOVE: Journal of Community Service and Engagement, 2022)
Natural resources and human resources of sukajaya village are very potential. This condition makes the reason to make sukajaya village as an example of an economically independent village supported by abundant produce. This community empowerment and training program aims to develop cassava processed products into churros food products that have better added value and can make the community have a prosperous independent economy. After this program is implemented, the result obtained is the development of cassava processed products into more innovative churros and the surrounding community better understand the flow of products from upstream to downstream by utilizing the potential around the environment.